Prognostic Biomarkers in Early-Stage B-CLL Patients - Vanya Popova; Vanya Slavcheva; Margarita Alexandrova; Tsvetan Lukanov; Silvia Naneva; Nikolay Tzvetkov (Journal of Biomedical & Clinical Research)
Chronic lymphocytic leukemia is one of the most common types of leukemia in adults. It belongs to the group of indolent lymphoproliferative disorders and has a slow clinical course. Approximately 50% of newly diagnosed patients do not require treatment for years. A better understanding of the pathophysiology of the disease has led to the development of models for assessment of the risk.Our study aimed to evaluate the prognostic significance of the serum marker beta-2 microglobulin (82M) and the flow cytometric marker CD49d in patients with early-stage of B-chronic lymphocytic leukemia (B-CLL) as well as look for a correlation between CD 49d and the early stages of the disease. For this purpose, analysis of 30 untreated patients with known and newly diagnosed B-CLL was carried out. The following methods were used: documentary, flow cytometric analysis of peripheral blood, Rai staging system and chi-square test of independence (Fisher’s Exact Test). The results from our study showed that a small number of patients in the early stage of the disease have high levels of CD49d expression and beta-2 microglobulins. In eight of 29 patients, the flow cytometric marker was higher than 30%, and in ten out of 29 patients, the B2M was above the reference range. No significant correlation between the two markers in early stage B-CLL patients was found.